The effects of developmental co-teaching on education trainees: A literature review - Fortier, Mélissa; Tremblay, Philippe (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2025)
This article provides a systematic review of the literature on developmental co-teaching. Developmental co-teaching appears as an alternative practice to traditional internships wishing to better meet the current needs of the community. Developmental co-teaching involves two trainees teaching the same group of students or one trainee and the classroom teacher. The main results show that the two models of developmental co-teaching contribute to improving the initial training of trainees both during the internship and in the longer term in their professional practice. These contributions include, among other things, the development of a collaborative and reflective vision of the profession as well as the development of the professional identity of the learner, a vision that traditional internships cannot provide.